2012
DOI: 10.1186/1556-276x-7-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crystallization and dopant concentration on the emission behavior of TiO2:Eu nanophosphors

Abstract: Uniform, spherical-shaped TiO2:Eu nanoparticles with different doping concentrations have been synthesized through controlled hydrolysis of titanium tetrabutoxide under appropriate pH and temperature in the presence of EuCl3·6H2O. Through air annealing at 500°C for 2 h, the amorphous, as-grown nanoparticles could be converted to a pure anatase phase. The morphology, structural, and optical properties of the annealed nanostructures were studied using X-ray diffraction, scanning electron microscopy, energy-dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
388
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,447 publications
(432 citation statements)
references
References 44 publications
44
388
0
Order By: Relevance
“…This peak broadening nature was caused due to the micro lattice strain at (101) lattice by Gd 3+ doping carriers which restrain the further growth of TiO 2 crystallites. 35,36 This fact suggested the successful incorporation of rare earth ions into the anatase lattice. The scanning electron microscope (SEM) images of pristine and Gd doped TiO 2 are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This peak broadening nature was caused due to the micro lattice strain at (101) lattice by Gd 3+ doping carriers which restrain the further growth of TiO 2 crystallites. 35,36 This fact suggested the successful incorporation of rare earth ions into the anatase lattice. The scanning electron microscope (SEM) images of pristine and Gd doped TiO 2 are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When silver is incorporated into the ZnS lattice, a strain may be induced into the system which can alter the lattice periodicity and decreases the crystallinity. 23 In the present study, the substrate temperature is maintained at a fixed value at 200 0 C for different Ag incorporation concentrations. So the decrease in crystallinity can be related to increase in Ag incorporation.…”
Section: Resultsmentioning
confidence: 99%
“…It also shows that traces mixed phases of Y 2 O 3 -, ZnO-, β-Bi 2 O 3 is present in this sample. Other doped samples with 0.5 wt% and 1 wt% as doping concentration show amorphous nature due to the distortion produced in the lattice [13]. It also has been observed that crystallite size decreases with dopant concentration [12].…”
Section: Xrdmentioning
confidence: 70%